Effectiveness of a school-based smoking cessation program for adolescents in Taiwan - individual intervention versus group intervention. (3rd July 2020) - Chang, Chai-Jan; Hsieh, Mi-Chih; Tseng, Yu-Fang; Tu, Hung-Pin; Wu, Ming-Yang; Li, Shu-Hua
ABSTRACT: Objective: The purpose of this study was to compare the effectiveness of two methods to intervene in adolescent smoking in Taiwan and evaluate quitting behavior 6 months later. Methods: A total of 143 adolescent smokers were randomly assigned to individual or group intervention. The participants completed a questionnaire with demographic information items and items based on the theory of planned behavior. Quitting success was measured after 6 months. Results: In all, 46 participants (32.2%) had successfully quit smoking at the 6-month follow-up. The individual intervention abstinence rate was significantly higher (41.7%) than that of the group intervention (25.3%). A multiple logistic regression analysis revealed intervention was positively related to quitting behavior. Smoking adolescents with low quitting intention had a higher quit rate following individual intervention, although pa high quitting intention was associated with a higher quit rate among group intervention participants. Conclusions: Both individual and group intervention greatly helped participants quit successfully. However, participants receiving individual intervention exhibited a higher success rate. Adolescent smokers with high quitting intention had remarkably similar success rates in either individual or group intervention. Adolescents with low quitting intention only achieved a high success rate in smoking cessation with individual intervention. Therefore, different interventions can be applied according to level of quitting intention.